ContExtended Questions (CEQ) to Teach and Assess Clinical Reasoning: A New Variant of F-Type Testlets - Kıyak, Yavuz Selim; Budakoğlu, Işıl İrem; Kula, Serdar; Coşkun, Özlem (Spanish Journal of Medical Education, 2021)
This study introduces ContExtended Questions (CEQ), which is a tool both to teach and assess clinical reasoning particularly in the preclinical years, and the web-based program to implement. CEQ consists of text-based case-based multiple-choice questions that provide patient data in a fixed and predetermined sequence. It enables the examinees to develop and reshape their illness scripts by using feedback after every question. Feedback operates to transform the examinee’s failure into a “productive failure”. The preliminary results of the randomized controlled experiment of teaching clinical reasoning to preclinical students through CEQ is quite satisfactory. In the medical education literature, this would be the first time that students, who have no or very limited clinical experience, developed their illness scripts just by taking formative multiple-choice tests. The approach would be named “test-only learning”. The complete results of the experiment and then more experiments in other contexts and domains are necessary to establish a more powerful assessment tool and software. Furthermore, by changing the content of the questions, it is possible to use CEQ in every period of medical education and health professions education.